A new all-purpose bilateral cleft lip repair: Bilateral cheiloplasty suitable for most conditions. Issue 4 (April 2018) - Baek, Rong-Min; Myung, Yujin; Park, Iehyon; Pak, Chang-Sik; Kim, Baek-kyu; Lâm, Vũ Ngọc; Jeong, Jae Hoon
Summary: Background: Only experienced surgeons can produce satisfactory results with most of the current surgical methods for bilateral cleft lip repair. The existing methods require not only preoperative orthodontic maneuvers but also accurate measurements for surgical design. We describe an easy-to-design and simple-to-execute general purpose surgical technique to repair most bilateral cleft lips. Methods: A retrospective review was performed for the patients who underwent bilateral cleft lip repair using our novel method between 2003 and 2016. The authors collected data from medical records, and the aesthetic results were judged using the aesthetic result categories by three independent surgeons; indirect anthropometry was applied to patients over 9 years of age. In addition, we investigated the complications, the reoperation rate, and the reasons for reoperation. Results: Bilateral cleft lip surgery was performed in 146 cases between 2003 and 2016. Seventy-eight patients had bilateral complete cleft lips, 47 patients had bilateral incomplete cleft lips, and 21 patients had bilateral complete and incomplete cleft lips (asymmetric patients). There were no acute complications requiring re-surgery, such as wound dehiscence, hematoma, and infection. According to aesthetic classification, 74 patients (51%) were classified into category I and 72 patients (49%) into category II; no patients were classified into categories III and IV. Seventy patients (48%) underwent secondary lip operations. In anthropometry, the measurements were observed to be symmetrical; left and right measurement data were not significantly different. The main purposes of the revision were excision of widened philtral scars (42 cases) and correction of lateral vermilion bulging (28 cases). Conclusions: We have found our novel technique to be simple and capable of providing consistent, reproducible, and reliable results.